2015
DOI: 10.7196/sajbl.8060
|View full text |Cite
|
Sign up to set email alerts
|

Biobanks and human health research: Balancing progress and protections

Abstract: The advent of biobanks in the field of science and technology has seen scientists entering a new age in biotechnology research. General ethical considerations, which apply to health research involving human participants, will apply equally to biobank research. However, in addition, there are unique ethical issues specific to biobank research. This is because of the nature of biobank research which has evolved to include an intersection of disciplines and networks. While the unique considerations pertaining to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Others include the Australian Guidelines on Human Biobanks and Genetic Research Databases 103 ; The OECD Principles and Guidelines for Access to Research Data from Public Funding 104 ; the Bermuda Principles 105 ; and the Expert Advisory Group on Access (EAGDA) report on Data Access 106 , 107 . Similar tools have been developed in parts of Africa 108 .…”
Section: Resultsmentioning
confidence: 99%
“…Others include the Australian Guidelines on Human Biobanks and Genetic Research Databases 103 ; The OECD Principles and Guidelines for Access to Research Data from Public Funding 104 ; the Bermuda Principles 105 ; and the Expert Advisory Group on Access (EAGDA) report on Data Access 106 , 107 . Similar tools have been developed in parts of Africa 108 .…”
Section: Resultsmentioning
confidence: 99%
“…that an 'ethico-regulatory framework' that is exclusively focused on biobanks [16] and in concurrence with all the principles of the UDBHR and international guidelines for biobanks should be developed and implemented in SA in the near future. [7][8][9] …”
Section: Resultsmentioning
confidence: 99%
“…informed consent, privacy and confidentiality, sharing of benefits, and many other ethical challenges. It is surmised that there are >12 biobanks of different sizes in SA, [7][8][9] but there is currently no national instrument that focuses exclusively on the ethics of biobanks. The National Health Act No.…”
Section: In Practicementioning
confidence: 99%
“…They further note that although some of the stakeholders have suggested that there should be host institution research capacity building in order to enable much of the research processes to be conducted locally, there is an acknowledgement that no level of local capacity can completely eliminate sample export. Dhai, Mahomed and Sanne (2015) argue that these challenges should not impede on human health research because networking and sharing of data maximise research potential through desired statistical power attainment, addressing resource constraint and some of the financial issues as well as being for the common good. It is for this reason that a mechanism for monitoring of the fate of exported samples is required.…”
Section: The Necessity Of a Mechanism For Monitoring Of The Fate Of E...mentioning
confidence: 99%